KDYMM Seri Paduka Baginda Yang di-Pertuan Agong spends time with UMP associates hands over donations to students - Mimi Rabita, Abdul Wahit (2023)
GAMBANG, 14 April 2023 - His Majesty Yang Maha Mulia Seri Paduka Baginda di-Pertuan Agong, Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Almarhum Sultan Haji Ahmad Shah Al-Musta’in Billah was pleased to spend time with Universiti Malaysia Pahang (UMP) associates and provide donations to 60 students here.